Analisis intensi dosen dalam implementasi Kurikulum berbasis kkni di iain kediri - Intan Nuyulis Naeni Pupitasari (Educatio, 2020)
The origin of Presidential Regulation No. 08/2012 concerning the Indonesian National Qualification Framework (KKNI) is oriented as a framework for qualifying the competency level of graduates who can juxtapose, equalize, and integrate education, training fields and work experiences. Each educational institution attempts to establish higher education that is able to produce graduates who have attitudes, knowledge, and skills that meet the expectations of the society and the stakeholders by implementing the KKNI-based curriculum. The teachers who become the primary sample in this study are the spearhead of the implementers in the process of implementing the curriculum in higher education. This research employs a quantitative approach with correlational design. Data collection was carried out through a questionnaire distributed to 109 IAIN Kediri teachers spread across all departments. Furthermore, the data were analyzed by using descriptive statistics, Pearson product-moment correlation, ANOVA, and multiple regression. Based on the analysis tool, it is known that the variables of attitude, subjective norms, and behavioral control simultaneously influence teachers 'intentions in the implementation of the IQF-based curriculum. However, it is found that only partially subjective norms and behavioral control variables bring a significant effect on teachers' intentions in implementing the KKNI-based curriculum at IAIN Kediri